Structural stability, optical and thermoelectric properties of the layered RbSn2Br5 halide synthesized using mechanochemistry - Abia, Carmen (2023)
Two-dimensional (2D) layered metal halide perovskites have recently received a lot of attention due to their possible applications as photovoltaic and optoelectronic materials. Rubidium di-tin pentabromide, RbSn2Br5, is a promising lead-free alternative to its RbPb2Br5 counterpart. Its lack of toxic lead, improved stability, and tolerance to ambient conditions are a great step forward to be used in electronic devices. In contrast with lead-based halides, this sample has received less attention up to now. There have been no experimental studies on its transport parameters such as electronic conductivity, Seebeck coefficient, or thermal transport. Here, we describe how this material can be easily synthesized using a ball milling procedure, obtaining specimens with high crystallinity. TG measurements indicate total decomposition above ∼673 K, whereas DSC curves suggest melting and recrystallization at 562 K (heating run, endothermic) and 523 K (cooling run, exothermic), respectively. A structural analysis from room temperature up to 548 K from neutron powder diffraction (NPD) data allowed the determination of the Debye model parameters, providing information on the relative Rb-Br and Sn-Br chemical bonds. Synchrotron X-ray diffraction experiments confirmed a tetragonal structure (space group I4/mcm) and provided evidence on the presence of the Sn2+ lone electron pair (5s2) from a X-N study. Diffuse reflectance UV-vis spectroscopy yields an indirect optical gap of ∼3.08 eV, coincident with the literature and ab initio calculations. A maximum positive Seebeck coefficient of ∼2.3 × 104 μV K−1 is obtained at 440 K, which is one order of magnitude higher than those reported for other halide perovskites. We obtain an ultra-low thermal conductivity, below 0.2 W m−1 K−1 from 300 up to 550 K.